Role of personal aptitudes as determinants of incident morbidity, lifestyles, quality of life, use of the health services and mortality (DESVELA cohort): qualitative study protocol for a prospective cohort study in a hybrid analysis - Yudy Young-Silva; Yudy Young-Silva; Anna Berenguera; Anna Berenguera; Anna Berenguera; Anna Berenguera; Constanza Jacques-Aviñó; Constanza Jacques-Aviñó; Constanza Jacques-Aviñó; Montserrat Gil-Girbau; Montserrat Gil-Girbau; Montserrat Gil-Girbau; et al. (Frontiers Media S.A., 2023)
IntroductionMaintaining or acquiring healthier health-oriented behaviours and promoting physical and mental health amongst the Spanish population is a significant challenge for Primary Health Care. Although the role of personal aptitudes (characteristics of each individual) in influencing health behaviours is not yet clear, these factors, in conjunction with social determinants such as gender and social class, can create axes of social inequity that affect individuals' opportunities to engage in health-oriented behaviours. Additionally, lack of access to health-related resources and opportunities can further exacerbate the issue for individuals with healthy personal aptitudes. Therefore, it is crucial to investigate the relationship between personal aptitudes and health behaviours, as well as their impact on health equity.ObjectivesThis paper outlines the development, design and rationale of a descriptive qualitative study that explores in a novel way the views and experiences on the relationship between personal aptitudes (activation, health literacy and personality traits) and their perception of health, health-oriented behaviours, quality of life and current health status.Method and analysisThis qualitative research is carried out from a phenomenological perspective. Participants will be between 35 and 74 years of age, will be recruited in Primary Health Care Centres throughout Spain from a more extensive study called DESVELA Cohort. Theoretical sampling will be carried out. Data will be collected through video and audio recording of 16 focus groups in total, which are planned to be held in 8 different Autonomous Communities, and finally transcribed for a triangulated thematic analysis supported by the Atlas-ti program.DiscussionWe consider it essential to understand the interaction between health-related behaviours as predictors of lifestyles in the population, so this study will delve into a subset of issues related to personality traits, activation and health literacy.Clinical trial registration: ClinicalTrials.gov, identifier NCT04386135.